Social Dynamics and Public Reactions to School Bullying: Evaluating Educational Policy Interventions - Dina Rahmawati; Pipian (Journal of Smart Pedagogy and Education, 2025)
This research evaluates social dynamics and public reactions to Indonesian school bullying during the implementation of Permendikbudristek Number 46 of 2023. Utilizing a Systematic Literature Review and qualitative content analysis, this study synthesizes Scopus data and national reports from 2020 to 2025. Findings show a surge in cases from 91 in 2020 to 573 in 2024, reflecting increased awareness alongside institutional failure. Although PPKSP regulations are theoretically comprehensive, effectiveness is hindered by insufficient teacher training, administrative burdens on Violence Prevention and Handling Teams, and cultural normalization of aggression. The digital panopticon phenomenon via social media accelerates institutional accountability but risks secondary victimization. Analysis indicates that bullying is not merely a behavioral defect but a reproduction of social power structures requiring restorative justice-based interventions. The study concludes that policy success depends on dismantling silence and integrating social-emotional competencies into curriculum to guarantee safe learning environments for achieving Golden Indonesia 2045 vision.